Factors associated with knowledge on the prevention of gastric cancer in patients at a hospital of Lima - Peru, 2017 - Berrospi Zavala, Mariela (2019)
Objective: To determine the factors associated with knowledge on the prevention of gastric cancer in patients attended at the external office of the Vitarte Hospital in September - November 2017. Methods: Cross-sectional, analytical and observational study. The sample consisted of 321 patients who met the selection criteria. The knowledge level test on gastric cancer prevention and the Graffar test was applied. The statistical software IBM SPSS version 23 was used to analyze the data. Results: 62% of the surveyed population obtained a medium level of knowledge. In addition, the association of the level of knowledge, work situation, access to the internet and the socioeconomic stratum was statistically significant (p = 0.019, p = 0.018, p = 0.001). Conclusion: It is concluded that the level of low and medium knowledge about gastric cancer prevention was significantly associated with having no occupation, not having access to the internet and belonging to a socioeconomic level IV and V. DOI:10.25176/RFMH.v19.n2.2064